Association between socioeconomic status and mucosal healing in Japanese patients with ulcerative colitis: a cross-sectional study. Issue 1 (19th October 2022) - Kitahata, Shogo; Furukawa, Shinya; Miyake, Teruki; Shiraishi, Kana; Tange, Kazuhiro; Hashimoto, Yu; Yagi, Sen; Ninomiya, Tomoyuki; Suzuki, Seiyuu; Shibata, Naozumi; Murakami, Hidehiro; Ohashi, Katsuhisa; et al.
Abstract : Objective: Socioeconomic status is a risk factor for worse outcomes in many diseases. However, evidence on the association between socioeconomic status and clinical outcome in patients with ulcerative colitis (UC) is limited. In the clinical setting, the therapeutic goal for UC is to achieve mucosal healing (MH). Thus, the aim of this study is to examine the association between socioeconomic status and MH in patients with UC. Methods: The study population consisted of 298 patients with UC. Education status and household income were divided into three groups based on a self-administered questionnaire. MH and complete MH were defined as a Mayo endoscopic subscore of 0–1 and 0, respectively. The association of socioeconomic status with MH and complete MH was assessed by multivariate logistic regression analysis. Patients with UC were divided into a younger group (<51 years old) and an older group (≥51 years old) based on median age. Results: The percentage of MH and complete MH was 62.4% and 25.2%, respectively. In all patients, socioeconomic status was not associated with MH and complete MH, respectively. In the older group, education but not household income was independently positively associated with MH and complete MH. In contrast, in the younger group, no association between socioeconomic status and MH and complete MH was found. Conclusion: In older Japanese patients with UC, education status but not household income was independently positively associated with MH and complete MH.